Developing a short form of the Awe Experience Scale (AWE-SF) in psychedelic samples - Graziosi, Marianna; Rohde, Julia Sarah; Lake, Stephanie; Lucas, Philippe; Kaufman, Scott Barry; Yaden, David Bryce (PLOS ONE, 2024)
This study aimed to develop and validate a short-form version of the AWE-S (AWE-SF) within psychedelic samples, to reduce participant burden while maintaining psychometric integrity. Across five studies, we first replicated the original six-factor structure of the AWE-S through exploratory and confirmatory factor analyses (Study 1), leading to the creation of the 12-item AWE-SF (Study 2–3). We then established the AWE-SF’s initial and predictive validity by correlating it with relevant emotional, psychedelic, and well-being outcomes (Study 4–6). The AWE-SF demonstrated strong positive associations with positive emotions and was also linked to openness to experience. Moreover, the AWE-SF effectively predicted both mystical-type and challenging psychedelic experiences, as well as long-term well-being outcomes such as life satisfaction and psychological richness. In particular, the facets of connection and vastness were associated with positive emotional states and mystical-type experience, while accommodation and self-loss were associated with negative emotional states and challenging psychedelic experience. These findings suggest that the AWE-SF is a robust, reliable, and accessible tool for measuring awe experience.